Design of a digital DC-DC converter - Guo, Jianhong. (2009)
Technological advancement has led to the creation of smaller and more sophisticated devices. The capability to maintain the reliability and stability of the DC-DC converters and regulating the low output voltage turn out to be a major concern for many researchers nowadays. In the recent years, major researches have been directed towards digital control which can offer higher flexibility, robustness and programmability in creating the next generation power converters.